Analisis Kemampuan Membaca dan Menulis Al-Quran pada Siswa Kelas VIII – A MTs Darul Arafah - Istihara Safitri; Silvia Utari; Muhammad Ilham (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This study aims to describe the ability of students in reading and writing the Quran at MTs Darul Arafah. The method used is field research with a qualitative approach, involving research subjects in the form of 19 students in class VIII, consisting of 10 male students and 9 female students. Data collection was carried out through tests, interviews, documentation, and observation, with assessment indicators including the accuracy of pronunciation of makharijul letters, the rules of tajweed science, and the length of short readings. The results showed that students' ability to read the Quran with makharijul huruf reached an average score of 75.6, which is included in the good category. The ability to read the Quran based on tajweed rules showed better results with an average of 80.3, including the excellent category. In addition, the ability of students to read the Quran by paying attention to the short length of the recitation also showed similar results, with an average score of 80.3, categorized as very good. This study indicates that despite challenges in reading and writing the Quran, overall, learners at MTs Darul Arafah show significant progress in important aspects of Quran learning. The findings are expected to provide insights for the development of curriculum and teaching methods for reading and writing the Quran in madrasahs.